FACTORS ASSOCIATED WITH CIVIC ENGAGEMENT IN ADOLESCENCE: THE EFFECTS OF NEIGHBORHOOD, SCHOOL, FAMILY, AND PEER CONTEXTS. Issue 8 (November 2016) - Rossi, Giulia; Lenzi, Michela; Sharkey, Jill D.; Vieno, Alessio; Santinello, Massimo
Abstract : Research on youth civic engagement has emphasized the importance of growing up in a civic context. We examined the relative influence of neighborhood characteristics (neighborhood opportunities and intergenerational closure), civic education at school, friends' civic engagement, and parents' civic engagement on civic attitudes and civic behaviors among youths. Participants were 403 11‐ to 15‐year‐old adolescents randomly selected from the city register of a midsized city in Italy. The hierarchical regression analysis found that all analyzed contexts were related to adolescent civic engagement. In particular, intergenerational closure, friends' civic engagement, and parents' civic engagement were associated with both civic attitudes and civic behaviors. Findings highlighted the importance of considering multiple contexts to understand what factors are associated with youth civic engagement. We discuss ways that findings can be transmitted into further research and practice to address the multiple contexts in which youths are embedded and their relative influence on adolescent civic engagement.